2017
DOI: 10.4236/as.2017.87050
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Carbon, Mineral-N and Soil Nutrients in Indigenous Agroforestry Systems and Other Land Use in the upper Solimões Region, Western Amazonas State, Brazil

Abstract: Slash and burn cultivation systems carried out by many farmers in the Amazon region lead to changes in biogeochemical cycles of nutrients. To assess the extent of the impact of shifting cultivation on the soil in a floodplain portion of this region, samples of an Inceptisol surface layer (0 -5 cm) under primary forest (FP), secondary forest at an advanced stage of recovery (FS), secondary forest at an initial stage of recovery (CAP), agroforestry (SAF), plantations (RÇ) in indigenous communities and small farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
1
0
1
Order By: Relevance
“…5 and Table 1), with a correlation value of 0.81. Villani et al (2017) verified that the two first components explained 94% of the total variance and that PC1 presented high correlations with MBC and the ammonium concentration in the soil, which was mainly related to the areas of forests, agroforests and pastures. Our results support the previous statements, indicating that the microbial biomass carbon represents the efficiency of the microorganism community in the soil in transforming the carbon from the deposited material.…”
Section: Discussionsupporting
confidence: 53%
“…5 and Table 1), with a correlation value of 0.81. Villani et al (2017) verified that the two first components explained 94% of the total variance and that PC1 presented high correlations with MBC and the ammonium concentration in the soil, which was mainly related to the areas of forests, agroforests and pastures. Our results support the previous statements, indicating that the microbial biomass carbon represents the efficiency of the microorganism community in the soil in transforming the carbon from the deposited material.…”
Section: Discussionsupporting
confidence: 53%
“…Although pH in roças increased after burning, it does not mean that pH in capoeiras (before burning) is low. In all sites of this study, the pH levels are much higher than in other slash‐and‐burn fields in Amazonia, where soil pH is mostly between 4 and 5, and despite it increases right after burning, it rarely reaches values above 6.5 or 7 as we observed here (Béliveau et al, 2015; Junqueira, Stomph, et al, 2016; Melo et al, 2006; Moreira et al, 2009; Silva Neto et al, 2019; Villa et al, 2018; Villani et al, 2017). However, in another indigenous land in this same savanna region, Melo et al (2010) found pH levels similar to this study (between 6 and 8), including slash‐and‐burn cultivation areas.…”
Section: Discussionsupporting
confidence: 76%
“…Although most studies emphasize that the main changes in soil fertility in slash‐and‐burn systems happen at depths up to 10 cm (Fachin et al, 2021; Lintemani et al, 2020; Silva Neto et al, 2019; Villani et al, 2017), we chose to use the depth of 0–20 cm because this is the main zone occupied by the roots of the main cultivated plants in studied area (corn and cassava), so we consider it as the better parameter to investigate in order to generate not only information for scientific purposes but also management recommendations for communities involved in this research, as will be discussed along this paper.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in Ca, Mg and P between the soils of the two land-use systems sampled (Table 1), contrary to what has been observed in other studies in the Amazon, which showed increases in these nutrients in the soils of AFSs in relation to nearby forests or other natural vegetation [13,22,23]. However, these other studies examined homegarden agroforestry systems, where nutrient inputs from domestic residues can have a significant effect on soil fertility over time.…”
Section: Soil Chemical Attributescontrasting
confidence: 63%